Recurrence rates of surgically resected solitary fibrous tumours of the pleura: a systematic review and meta-analysis. (22nd April 2021) - Liu, Wan-Li; Wu, Wei; Hong, Qiong-Chuan; Lv, Kun
Abstract:  : OBJECTIVES: Recurrence rates of solitary fibrous tumours of the pleura (SFTP) after surgical resection vary widely in the published literature. Our objective was to systematically review the existing literature to determine an accurate estimate of SFTP recurrence rates after surgical resection and to determine risk factors associated with recurrence. METHODS: PubMed, EMBASE and the Cochrane library were systematically searched for randomized controlled trials and observational studies (prospective or retrospective) through 20 June 2020 that reported the recurrence rates after surgical resection. The outcome of interest was recurrence. RESULTS: Of the 23 included studies comparing 1262 patients, the overall recurrence of SFTP in patients who underwent surgical resection was 9% [95% confidence interval (CI) 7–12%; I 2 = 52%]. In addition, pooled benign and malignant recurrence rates were 3% (95% CI 2–5%; I 2 = 8%) and 22% (95% CI 15–32%; I 2 = 52%), respectively. A benign SFTP was associated with a significantly lower recurrence rate than a malignant SFTP [odds ratio (OR) 0.11; 95% CI 0.06–0.20; I 2 = 0%]. There was no significant difference in the recurrence rates between lesions originating from parietal versus visceral pleura (OR 1.30; 95% CI 0.28–6.02; I 2 = 59%). Female sex was associated with increased recurrence (OR 5.29; 95% CI 1.66–16.92; I 2 = 0%). CONCLUSIONS: Collectively, this systematic review demonstrated a 9% SFTP post-resection recurrence rate. Furthermore, the recurrence rates for benign and malignant SFTP were 3% and 22%, respectively. Histological malignancy and female sex were associated with higher risk.